Long-term survival and cure fraction estimates for childhood cancer in Europe (EUROCARE-6): results from a population-based study. Issue 12 (December 2022) - Botta, Laura; Gatta, Gemma; Capocaccia, Riccardo; Stiller, Charles; Cañete, Adela; Dal Maso, Luigino; Innos, Kaire; Mihor, Ana; Erdmann, Friederike; Spix, Claudia; Lacour, Brigitte; Marcos-Gragera, Rafael; et al.
Summary: Background: The EUROCARE-5 study revealed disparities in childhood cancer survival among European countries, giving rise to important initiatives across Europe to reduce the gap. Extending its representativeness through increased coverage of eastern European countries, the EUROCARE-6 study aimed to update survival progress across countries and years of diagnosis and provide new analytical perspectives on estimates of long-term survival and the cured fraction of patients with childhood cancer. Methods: In this population-based study, we analysed 135 847 children (aged 0–14 years) diagnosed during 2000–13 and followed up to the end of 2014, recruited from 80 population-based cancer registries in 31 European countries. We calculated age-adjusted 5-year survival differences by country and over time using period analysis, for all cancers combined and for major cancer types. We applied a variant of standard mixture cure models for survival data to estimate the cure fraction of patients by childhood cancer and to estimate projected 15-year survival. Findings: 5-year survival for all childhood cancer combined in Europe in 2010–14 was 81% (95% CI 81–82), showing an increase of three percentage points compared with 2004–06. Significant progress over time was observed for almost all cancers. Survival remained stable for osteosarcomas, Ewing sarcoma, Burkitt lymphoma, non-Hodgkin lymphomas, and rhabdomyoscarcomas. For all cancers combined, inequalities still persisted among European countries (with age-adjusted 5-year survival ranging from 71% [95% CI 60–79] to 87% [77–93]). The 15-year survival projection for all patients with childhood cancer diagnosed in 2010–13 was 78%. We estimated the yearly long-term mortality rate due to causes other than the diagnosed cancer to be around 2 per 1000 patients for all childhood cancer combined, but to approach zero for retinoblastoma. The cure fraction for patients with childhood cancer increased over time from 74% (95% CI 73–75) in 1998–2001 to 80% (79–81) in 2010–13. In the latter cohort, the cure fraction rate ranged from 99% (95% CI 74–100) for retinoblastoma to 60% (58–63) for CNS tumours and reached 90% (95% CI 87–93) for lymphoid leukaemia and 70% (67–73) for acute myeloid leukaemia. Interpretation: Childhood cancer survival is increasing over time in Europe but there are still some differences among countries. Regular monitoring of childhood cancer survival and estimation of the cure fraction through population-based registry data are crucial for evaluating advances in paediatric cancer care. Funding: European Commission.